A regression model for vessel turnaround time - Mokhtar, Kasypi; Shah, Muhammad Zaly (2006)
Turnaround time in port industry portrays capability and ability of container terminal in providing services. This study is motivated by the rapid development in port container terminal, in providing efficient and effective services and high port productivity, with the aim to achieve optimum port performance. Research arises from the issue between port throughputs (i.e. Teus- Twenty Footer Equivalent Unit) and port facilities (e.g. quay crane, prime movers etc), as currently it is not possible to determine significant factor(s) that influence port performance, in terms of turnaround time. For this purpose, the research proposes a regression model that relates these variables, i.e. turnaround time and port facilities. Two ports in Port Klang – Westport and Northport – are used as the subjects from which actual vessel call data collected between August 1 and August 31, 2005 are used. The results show that vessel turnaround time is highly correlated with crane allocation as well as the number of containers loaded and discharged. The benefits of such model include giving port operators opportunity to determine optimum crane allocation to achieve the desired turnaround time given the quantity of containers to be processed.